Mechanical Performance of Epoxy Composite Reinforced with Wood Dust and Crumb Rubber Waste - Imran, Al Ichlas; Siregar, Januar Parlaungan; Cionita, Tezara; Fitriyana, Deni Fajar; Anis, Samsudin; Dewi, Rozanna; Junaedi, Thomas; Wijayanto, Etanto Heiliano; Prayogo, Wisnu (Advance Sustainable Science Engineering and Technology, 2025)
The incorporation of wood dust and crumb rubber waste as filler in polymer matrix composite still requires in-depth evaluation of mechanical properties because they have different characteristics. This study evaluates the tensile, flexural, and hardness properties of epoxy composites reinforced with various fractions of wood dust and crumb rubber (5, 10, and 15%). The results showed that the composite with 5% crumb rubber produced the highest tensile strength of 15.52 MPa (CR5), while the highest flexural strength was 30.46 MPa (CR10), and the highest hardness was 75.9 HRC (CR15), indicating superior performance for CR fillers. The observations of the fracture surface showed that increasing the fraction of wood dust contributed to lowering the mechanical performance due to the relatively large distribution of voids and agglomeration. This finding confirms the importance of filler type and fraction selection on composite performance. Future research is recommended to explore filler surface modification and hybrid combinations to improve dispersion and bonding between phases in composites.